Use of statins in cardiorenal syndrome : possibilities for its treatment and prevention - A. M. Minasyan (Klinicist)
Cardiovascular diseases are the major cause of disease and death not only in the general population, but also in patients with chronic kidney disease. The growing morbidity and mortality from chronic kidney disease and chronic heart failure conduce to an increase in cases of cardiorenal syndrome. Along with angiotensin-converting enzyme inhibitors, β-adrenoblockers, antianemic drugs, and diuretics, statins are appropriate and recommended by a number of trials for the prevention and treatment of the cardiorenal syndrome. Statins are effective in preventing the cardiorenal syndrome in patients at its high risk, improve quality of life and survival; in predialysis patients with chronic kidney disease, they may be secondary prevention of cardiovascular death.